Analysis of the Family Hope Program in Sidoarjo Regency - Lestari, Dwi Sri; Sukmana, Hendra (Universitas Muhammadiyah Sidoarjo, 2020)
The analysis technique in this study is a qualitative analysis type, referring to the theory of Miles and Huberman. The results showed that the Analysis of the Family Hope Program in Sidoarjo Regency according to the theory of public policy management, the first aspect of planning is according to Law No. 11 of 2009 and Presidential Regulation No. 15 of 2010 concerning the acceleration of Poverty Reduction. The organizing and implementation aspects consist of: (1) the coordination team at the Regency/City level, (2) the sub-district level, and (3) the implementers of activities accompanying the program and the community. Aspects of supervision are carried out at each stage of distribution and/or as needed. Evaluation of the distribution of PKH Social Assistance is carried out to measure the success or failure of the implementation of the distribution of PKH Social Assistance. Supporting factors in the implementation of the Family Hope Program in Sidoarjo Regency include the existence of a strong commitment between the central and local governments to make the Family Hope Program a success (PKH) and the existence of clear rules regarding the mechanism of program implementation as well as the guarantee of obtaining proper health and education from the government through social services. Meanwhile, there are still many residents who have not been registered in the PKH program and officers are not updating the data on prospective recipients of the PKH program, Key words: Public policy, Family Hope Program